2014
DOI: 10.1093/abbs/gmu072
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biochemical association of phycobilisome with photosystems in cyanobacterial state transition

Abstract: State transition is a short-term balance mechanism of energy distribution between photosystem II (PSII) and PSI. Although light-induced state transition in cyanobacteria has been suggested to depend completely on the phycobilisome (PBS) movement between PSII and PSI, the biochemical evidence has not been clearly shown. In this study, we locked the association of PBS with PSII or PSI using glycinebetaine when cells attain State 1 or 2 by exposure to light of blue or green, respectively. Subsequently, the PBS-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The possible diffusion of PBS along the thylakoid membrane was first showed by fluorescence recovery after photobleaching (FRAP) experiments in Dactylococcopsis salina and S. elongatus, showing that PBS-photosystem association is a dynamic process which depends on weak interactions with membrane lipids. 86,87 Based on FRAP experiments and to the possible association of PBSs with PSI and PSII, 57,82,94 the hypothesis of a light-harvesting complex moving and modulating the energy reaching each photosystem, analogous to plant and green algae state transitions, has frequently been proposed (Fig. 4).…”
Section: Pbs Mutants Impaired In State Transitionsmentioning
confidence: 99%
“…The possible diffusion of PBS along the thylakoid membrane was first showed by fluorescence recovery after photobleaching (FRAP) experiments in Dactylococcopsis salina and S. elongatus, showing that PBS-photosystem association is a dynamic process which depends on weak interactions with membrane lipids. 86,87 Based on FRAP experiments and to the possible association of PBSs with PSI and PSII, 57,82,94 the hypothesis of a light-harvesting complex moving and modulating the energy reaching each photosystem, analogous to plant and green algae state transitions, has frequently been proposed (Fig. 4).…”
Section: Pbs Mutants Impaired In State Transitionsmentioning
confidence: 99%
“…PBSs are only functionally intact in the presence of high phosphate buffer or its variant buffers, , making interrogations on protein conformational changes of PBS in solution very difficult. In my previous report, it was successfully revealed that PB-loop, an IDR in ApcE, is in structural proximity with ApcG, forming a protrusion toward the thylakoid membrane where two photosynthetic RCs are located .…”
Section: Resultsmentioning
confidence: 99%
“…All PPCs comprise a set of chromophores (or pigments) held in a well-defined protein scaffold. Phycobilisomes (PBSs), giant PPCs with a molecular mass range of 5–15 MDa, supply excitations to both photosystem I (PSI) and photosystem II (PSII). PBSs are highly organized assemblies of pigmented phycobiliproteins and pigmentless linker polypeptides. , …”
Section: Introductionmentioning
confidence: 99%